Trends in Financial Ratio Disclosure in Annual Reports: Content Analysis of Information Needs for Investor - Lindah Lindah; Randy Kuswanto (Dinasti Publisher, 2025)
The aim of this article is to analyze the annual reports of companies included in the LQ45 index from 2022 to 2024, with a particular focus on the boards of directors and commissioners, and to compare these with financial ratios and management reports. One way for businesses to communicate their financial information to interested stakeholders is by publishing financial reports. However, these reports alone do not always provide a comprehensive picture of the company's overall financial performance. To obtain a clearer insight into a company’s financial performance, financial ratios are used as analytical tools in the evaluation of financial reports. This article's goals are to (1) identify the most widely used and interesting ratios among investors and (2) summarize the findings from the examination of the reports submitted by the boards of directors and commissioners. This study employs a frequency-based research approach and utilizes quantitative data. The findings of this article offer an overview of the analysis of board of directors and commissioners' reports, along with fifteen commonly reported financial ratios found in the annual reports of companies listed on the LQ45 index from 2022 to 2024. We have shown that investors can benefit from financial ratio information and management reports when making decisions.